Priorities in the Cardiovascular Care of Breast Cancer Survivors - Ky, Bonnie (J Oncol Pract, 2018)
Breast cancer is the most common malignancy in women with more than 3 million breast cancer survivors in the United States alone. Survivors of breast cancer suffer from an increased burden of cardiovascular risk factors and disease. The focus of this review is to describe the epidemiology of cardiovascular disease in breast cancer survivors, including the cardiovascular concerns observed with common cancer therapies. Strategies to improve upon the early detection and treatment of cardiovascular disease, including clinical prediction algorithms, biomarkers, and imaging measures are also reviewed, and the use of cardioprotective therapies to mitigate risk are summarized. Finally, the need for evidence-based research to inform and improve upon the multidisciplinary care of this growing population is highlighted.